Physical activity types among US adults with mobility disability, Behavioral Risk Factor Surveillance System, 2017 - Hollis, NaTasha D. (Disabil Health J, 2020)
BACKGROUND: The Physical Activity Guidelines for Americans, second edition, recommend that all adults participate in moderate-intensity equivalent aerobic physical activity at least 150–300 min/week for substantial health benefits and muscle-strengthening activities involving all major muscle groups 2 or more days a week. The prevalence of the general population meeting the Guidelines and the types of physical activity in which they engage have been described elsewhere. Similar descriptions are lacking for individuals with mobility disability whose physical activity profiles may differ from the general population. OBJECTIVE: This study examined patterns of aerobic and muscle-strengthening physical activity among US adults with mobility disability. METHODS: We used 2017 Behavioral Risk Factor Surveillance System data from 66,635 adults with mobility disability. We estimated the percentage who engaged in any aerobic physical activity, met the aerobic and/or muscle-strengthening guidelines, and who participated in specific activities. RESULTS: Less than half (45.2%) of US adults with mobility disability reported engaging in aerobic physical activity, and 39.5% met one or both components of the physical activity guidelines. Walking was the most commonly reported activity type (34.0%). CONCLUSIONS: Walking is a common activity type among adults with mobility disability. Efforts to make walking or wheelchair rolling a safe, viable option are important to helping decrease barriers that may limit the ability of those with mobility disability to engage in walking or other physical activity types.